Parental acceptance of brain health programs for preschool children: a mixed-methods study exploring barriers, facilitators and future approaches - Lily A. Montague; Susan Hespos; Erin Mackenzie; Joyce Siette (Frontiers Media S.A., 2024)
BackgroundRecent research proposes that as much as 40% of dementia risk is amendable. Promoting healthy lifestyle behaviors in early life through educational methods can cultivate habits that may decrease dementia risk in later life. This study explores parental acceptance of brain health programs tailored for preschool children, aiming to identify barriers and facilitators affecting parental and child engagement.MethodsMixed-methods cross-sectional study. Urban and suburban parents (N = 187, Mage = 37.3 SD = 5.53, range = 29) of children aged three to five years across Australia. Parents participated in an online survey containing both open and closed questions exploring their personal views and opinions on brain health programs for their preschool children. Descriptive statistics, multiple linear regression analyses, and thematic analysis were used to explore sociodemographic factors associated with parental program acceptance.ResultsMost participants accepted a brain health program with over 98% agreeing a program would be useful for their child(ren). Participants with younger aged children were more likely to exhibit acceptance of a program (β = −0.209, p = 0.007). Three main categories emerged: dual home and preschool environments, the need for engaging brain health programs that were hands-on and screen-free, and addressing key barriers such as time and financial constraints to support implementation.ConclusionParticipants valued educating their children for a healthy life and viewed brain health programs favorably. This study contributes to early childhood education discussions, offering guidance for future generations' brain health and wellbeing.